Speed Limit Changes and Driver Behaviour: A Spatial Lag Model - Catherine Toulouse; Saeid Amiri; Marie-Soleil Cloutier; Nicolas Saunier (Findings)
Speed is a major factor in road safety and the interplay of the different factors affecting speed choice is not completely understood. This paper presents a study of operating speeds in Quebec, Canada, between 2000 and 2018 on provincial highways (except freeways) in response to speed limit changes. This paper shows that driving speed is spatially correlated. Two statistical models are then compared, with and without a spatial component. The spatial model provides a better fit and demonstrates that speed behaviour is spatially correlated. The resulting models confirm that drivers only partly adjust their speeds after a change and that several road features like side curbs, lateral and median strips are associated with driving speed.